2010
DOI: 10.1074/jbc.m110.112987
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Peptidoglycans Induce Excessive Activation of the Innate Immune System in Silkworm Larvae*

Abstract: Porphyromonas gingivalis, a pathogen that causes inflammation in human periodontal tissue, killed silkworm (Bombyx mori, Lepidoptera) larvae when injected into the blood (hemolymph). Silkworm lethality was not rescued by antibiotic treatment, and heat-killed bacteria were also lethal. Heat-killed bacteria of mutant P. gingivalis strains lacking virulence factors also killed silkworms. Silkworms died after injection of peptidoglycans purified from P. gingivalis (pPG), and pPG toxicity was blocked by treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…Pseudomonas aeruginosa activates the JNK-dependent caspase pathway through a type III secretion system (44,45). We recently reported that live and heat-killed Porphyromonus gingivalis, a human orthodontic pathogen, causes excessive activation of an immune reaction called melanization in the silkworm hemolymph, leading to the overproduction of reactive oxygen species and activation of caspases in larval tissues (46). In contrast, we did not observe extensive melanization in the hemolymph of silkworms injected with live S. marcescens.…”
Section: Discussionmentioning
confidence: 40%
“…Pseudomonas aeruginosa activates the JNK-dependent caspase pathway through a type III secretion system (44,45). We recently reported that live and heat-killed Porphyromonus gingivalis, a human orthodontic pathogen, causes excessive activation of an immune reaction called melanization in the silkworm hemolymph, leading to the overproduction of reactive oxygen species and activation of caspases in larval tissues (46). In contrast, we did not observe extensive melanization in the hemolymph of silkworms injected with live S. marcescens.…”
Section: Discussionmentioning
confidence: 40%
“…It is plausible that live fungal cells proliferate in the cricket body and the proliferated fungal cells kill crickets in the same manner as the heatkilled cells. In silkworms, β-glucan, a component of the fungal cell wall, excessively activates the humoral immune system, which kills silkworms (54,55). To optimize the utility of the two-spotted cricket as an animal infection model of human pathogenic fungi, further studies are needed to investigate the immune response of crickets against fungal cells and to reveal the molecular mechanism underlying infection-induced death in crickets.…”
Section: Discussionmentioning
confidence: 99%
“…In general, wet weights of vegetation are measured and compared in each group; however, we modified the protocol to measure the impaired valve tissue rather than the vegetation itself. It has been reported that only 0 to 10 mg of vegetation is typically collected from heart valve specimens (42,56,57). The resulting values were regarded as too small to compare and could show false-negative results.…”
Section: Figmentioning
confidence: 99%
“…Recently, larvae of the wax worm G. mellonella were used as a model of systemic bacterial infection, based on evidence of a correlation with mammals (42). Therefore, the virulence of S. mutans strains was evaluated using this model.…”
Section: Distribution Of Strains Expressing Cbp and Pamentioning
confidence: 99%